What is the general Chinese public's awareness of and attitudes towards Helicobacter pylori screening and associated health behaviours? A cross-sectional study. Issue 1 (25th January 2022) - Wang, Ying-xin; Zou, Jin-yu; Hu, Li-feng; Liu, Qi; Huang, Ruo-lin; Tang, Tian; Yue, Qian-qian; Sun, Ying-xue; Xiao, Qiao; Zeng, Xi; Zeng, Ying
Abstract : Objective: To evaluate the general population's awareness of and attitudes toward Helicobacter pylori (HP) screening and health behaviours. Design: Cross-sectional study. Setting: Hengyang, Hunan Province, China. Participants: Using stratified cluster random sampling, a pretested structured questionnaire was used to interview members of the general population aged ≥18 years. Primary and secondary outcome measures: Knowledge of and attitudes toward HP screening and associated health behaviours, sociodemographic factors associated with HP knowledge, and screening behaviours. Results: This study featured 1042 participants. The average knowledge score was 11 (QL =4, QU =20, range 0–29). Approximately 68.9% of the participants said they had heard of HP, but 67.5% had never had an HP test. The most common reasons for not undergoing screening were 'no symptoms' (55.7%) and 'lack of knowledge regarding the benefits of the test' (21.1%). Independent factors related to knowledge included age, education level, occupation, HP infection, frequency of drinking unboiled water (p<0.05). Factors independently associated with screening behaviour included occupation, average monthly income, presence/absence of indigestion, stomach discomfort or pain, and/or stomach disease and knowledge score (p<0.05). Overall, 941 (90.3%) participants never used anti-HP toothpaste, and 442 (40.5%) never used serving spoons or chopsticks. The risk factors for HP infection included eating out and eating in groups (p<0.05). Conclusion: In China, the general population has poor knowledge of HP, but most people have a positive attitude towards HP screening. Being asymptomatic and lacking knowledge about testing were the main reasons for reluctance to be screened. These results highlight the urgent need for educational activities to raise awareness, enhance screening rates for HP, and encourage people to adopt a healthy lifestyle.